(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg heSJMbI bO JbOe dfG ai cJGHfG gPG cJGHGf CMOgeG jYQa HGdMGUd hGdCNQ jYQa HGdYjf hbO QSefG cJGHfG gPG hSejfGg HcJGH GdfbO dCfg jMhi gPg GdCTjGA GdJi jfHYi ddEfSGf Cf jHMK YfgG s
(3BNQgG (B:s
(3hbO aSQfG CeQgeG CjVkG ai cJGH ef gPg cJHfG GdSHYI ai GdYjf hCRd GdTjWGf Yf bdHc hGdTc GdeJUhQ dfaSc Je cJGH GdfbO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs